A study on UTM mechanical engineering students' difficulties in reading an English engineering text - Norhidayah Daud, 1986-; Norazman Abdul Majid; Fakulti Pendidikan (2010)
Project Paper (Sarjana Muda Sains serta Pendidikan (Pengajaran Bahasa Inggeris sebagai Bahasa Kedua)) - Universiti Teknologi Malaysia, 2010